A procedure for the evaluation of occupational risk factors and their impact on work performance among users of data display screens (DDSS) - Real, Grether (2020)
The objective of this research is to propose a procedure that allows the evaluation of occupational risk factors and their impact on the work performance of DDS users. The research considered exploratory, descriptive, fieldwork and synthesis analysis methods. The procedure consisted of four stages: diagnosis of the current situation, risk assessment, incidence of risks in work performance, and risk control. Its main contribution lies in the compilation, selection, proposal and explanation of the tools that allow studying different workers whose activities are focused on the use of DDS.